Stable isotopes reveal dietary shifts associated with social change in Hellenistic, Roman and Late Antique Knossos. (October 2022) - Moles, Anna C.; Reade, Hazel; Jourdan, Anne-Lise; Stevens, Rhiannon E.
Highlights: Diet at ancient Knossos, Crete, in Greece changed in line with major social changes. Stable isotope analysis of human remains highlights dietary changes. Most people at Knossos were eating some meat or other animal products. Females had wider ranging isotopic values than males. Fish or seafood consumption increased in Late Antiquity. Abstract: Knossos was an important city on Crete and within Mediterranean networks in terms of trade and political status, though its status differed throughout the Hellenistic, Roman and Late Antique periods. This paper uses stable carbon and nitrogen isotope analysis to consider whether people at Knossos had differential diets due to the social, political, cultural, and economic changes across this time frame, factoring in age, sex and social status. Samples of human bone were selected to represent this range of time periods and variables. In this initial study, a small but insignificant increase in δ 13 C values was observed between the Hellenistic and Roman periods and there was a significant increase in δ 15 N values for the Late Antique period. No relationship between δ 13 C or δ 15 N and age was observed and while the female and male means were similar, the females had wider ranging values. No significant differences were detected by social status as represented by tomb type but there were small sample sizes for several of the tomb types. The results indicated a C3 terrestrial diet with meat or other animal products included for most individuals. The slight increase in δ 13 C values in the Roman period may represent either the introduction of a small amount of C4 plant or marine food, or very low trophic level marine foods into some Roman diets. The higher δ 13 C and, in particular, δ 15 N values observed in the Late Antique samples, suggests an increased consumption of seafood, potentially linked to Christian dietary practices or advances in fishing technologies and preservation techniques. The wider spread values of females compared to males, indicating a more varied diet, could have resulted from differential participation in religious institutions connected to food or may have been caused by greater nutritional stress in females in relation to pregnancy and reproductive issues. This study does not show a pattern of higher animal protein consumption in times of economic and cultural growth and prosperity but differences were detected between the different time periods in connection with the concurrent socio-economic changes.